Analisa Dampak Capaian Kompetensi Guru Terhadap Kinerja Guru - Novrian Satria Perdana (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The purpose of this study is to analyze the impact of teacher competence on teacher performance. In this research using quantitative approach with influence test method. The number of samples is 160 teachers in 16 schools of elementary school, junior high school, and SMK selected randomly in Jakarta. The sampling of this research using cluster sampling method technique. In this study using questionnaires instrument filled by teachers as research data. The data collected on this research variable is analyzed by using regression analysis technique. The conclusions of this study are (1) there is a significant, strong and positive impact on teachers' pedagogic competencies on teacher performance, and (2) there is a significant, strong and positive impact of teacher professional competence on teacher performance..